Preference Reversals Between Digital and Physical Goods. (April 2022) - Catapano, Rhia; Shennib, Fuad; Levav, Jonathan
The proliferation of digital goods has led to an increased interest in how the digitization of products and services affects consumer behavior. In this article, the authors show that although consumers are willing to pay more for physical than digital goods, this difference attenuates—and even reverses—when consumers are asked to make a choice between the two product formats. This effect is explained by a contingent weighting principle: In willingness to pay, a quantitative task, consumers anchor on quantitative information (e.g., market beliefs). However, in choice, a qualitative task, consumers anchor on qualitative information (e.g., which good dominates on the most important attribute). These differences in contingent weighting result in physical goods being preferred in willingness to pay, but their digital equivalent being preferred relatively more in choice. The authors draw conclusions from ten preregistered experiments and six supplemental studies using a variety of goods in hypothetical and incentive-compatible contexts, as well as within- and between-subjects designs. The article concludes with a discussion of implications for the marketing of digital goods.